TESS Light Curves of Cataclysmic Variables. VI. Intermediate Polars - Albert Bruch (The Astrophysical Journal Supplement Series, 2025)
The long and (almost) continuous high-cadence light curves provided by the TESS space mission are ideally suited to study in detail brightness variations in stellar sources on the broad range of timescales between minutes and months. By applying Fourier techniques, even low-amplitude coherent variations in noisy data can be identified, and their periods can be measured with high accuracy. Here, the available TESS light curves of all intermediate polars (IPs) and candidates listed on Koji Mukai’s Intermediate Polar Home Page and in the Ritter & Kolb catalog are subjected to a frequency analysis. A total of 121 systems are studied. In about half of them—mostly confirmed IPs, but also some candidates—variations caused by the white dwarf (WD) rotation are detected allowing the determination of precise periods. Comparison with previous measurements permitted, in some cases, confirming or newly uncovering period variations. The relative strength of the WD spin signals, their orbital sidebands, and overtones in power spectra—having the potential to shed light on the structure of emission, reflection, and reprocessing sites and their variations over time in the IP systems—was measured. Apart from IP-type variations, a wealth of other periodic or aperiodic brightness changes was observed in many of the target stars and is documented here. This includes refined or newly detected orbital periods, the temporal evolution of waveforms, superhumps, quasiperiodic oscillations, short-timescale (<1 day) bursts, coherent variations of an unidentified origin, and other sometimes enigmatic phenomena.